Effect of Zinc Oxide on Structural and Optical Properties Borotellurite Glass: Ternary Glass - Aso F. Mohamed; Saman Q. Mawlud (Zanco Journal of Pure and Applied Sciences, 2023)
A series of zinc borotellurite glass with the composition of (70-x)TeO2-30B2O3-xZnO (0= x ≥ 20) have been successfully synthesized by melt quenching techniques. Physical parameters such as density, molar volume and refractive index have been calculated, and maximum values of refractive index and density were obtained at 2.315 and 4.57, respectively. The amorphous nature of the glass sample was confirmed using the X-ray diffraction (XRD) technique; no sharp pick was observed in the XRD pattern, which confirms that the glass sample structure has amorphous nature. The absorption spectra were studied by using a UV-Vis-NIR spectrometer, and the values of direct band gap (Edir), indirect band gap (Eind) and Urbach energy (Eu) were obtained through the absorption edge studies. It was found that the values were between 3.54 and 3.69 eV and the values of lies between 3.33 and 3.51 eV. The Eu values lie between 0.17 to 0.21 eV. The bonding parameters of the glasses were analyzed by using Fourier Transform Infrared (FTIR) technique, and the formation of non-bridging oxygen (NBO) was observed, which indicates the presence of TeO4, BO3 and BO4 units.